1995
DOI: 10.2527/1995.733750x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of beef tenderness and quality traits with calcium chloride injection in beef loins 48 hours postmortem

Abstract: Boneless strip loin subprimals (n = 24) were fabricated from 12 USDA Standard yield grade 2 carcasses at a commercial beef processing facility and processed 48 h postmortem to determine the effect of injection of 200 or 250 mM calcium chloride (CaCl2) solution at 5% (wt/wt) on beef quality traits. One-third of the subprimal served as the control; the remaining portion was injected with either 200 or 250 mM CaCl2 at 5% (wt/wt). The CaCl2 concentration treatment was randomly assigned to strip loins fabricated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
9

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 7 publications
2
32
0
9
Order By: Relevance
“…Procedeu-se à remoção de quatro amostras de 1,27cm de diâmetro, as quais foram cisalhadas ao meio no equipamento Warner-Bratzler Shear modelo 3000, conforme metodologia de Kerth et al (1995).…”
Section: Methodsunclassified
“…Procedeu-se à remoção de quatro amostras de 1,27cm de diâmetro, as quais foram cisalhadas ao meio no equipamento Warner-Bratzler Shear modelo 3000, conforme metodologia de Kerth et al (1995).…”
Section: Methodsunclassified
“…Calcium chloride is added to muscle foods because of its ease of application, safety of use (approved by Food and Drug Administration) and as an additional source of calcium (Jaturasitha et al, 2004). It has been suggested to accelerate the tenderization process in the muscles (Morgan et al, 1991;Boleman et al, 1995;Kerth et al, 1995). Perez et al (1998) reported improved tenderness of meat obtained from chicken, horse, cattle and rabbit by calcium chloride injection.…”
Section: Introductionmentioning
confidence: 99%
“…The calpain is activated by Ca 2+ , indicating the role of the intracellular Ca 2+ concentration on the tenderness. The effect of Ca 2+ on tenderisation is manifested by several investigations injecting Ca 2+ (KERTH et al, 1995), marinating meat in Ca 2+ containing solutions (YOUNG and LYON, 1997), or inducing Ca 2+ release by high pressure (OKAMOTO et al, 1995). The rate of glycolysis affects the extend of the tenderisation at least in beef.…”
Section: Camentioning
confidence: 99%